Cleopatra in Italian and English Renaissance drama - Montanari, Anna Maria (Renaissance history, art and culture, 2019)
This book considers some of the main adaptations of the character of Cleopatra for the Renaissance stage, traveling from Italy to England to arrive finally to Shakespeare. It shows how each reading of the story of Cleopatra is unique to and expressive of the culture which produced it, even as writers drew from the same sources from Antiquity. For the first time texts belonging to different cultures, rigorously presented, are brought into dialogue on such questions as moral standpoint, gender and the representation of the exotic. Moreover, through the fascinating figure of Cleopatra, the reader is able to explore the development of Renaissance tragedy, in its commercial and non-commercial versions. Ultimately both questions at the heart of this study - concerning Cleopatra's identity and her translation into theatre - converge to be (dis)solved by Shakespeare.